Correlation between outpatient medical adherence and diabetic complications in patients with type 2 diabetes - Jeun Seo, Bum; Joon Lee, Mi (International Journal of Engineering and Technology, 2019)
The purpose of this study was to investigate the effect of medication adherence on diabetic complications in 19,317 outpatients aged 30 years or older who were diagnosed with type 2 diabetes mellitus and took oral hypoglycemic agents. Data was analyzed from National Health Insurance Service's standard cohort database from 2002 to 2013. For the incidence of diabetic complications, there was significant difference between insurance type, income level and the higher the age, the higher the incidence. In the Kaplan-Meier survival function, the group with higher medication adherence had higher survival probability for diabetic complications than the group with lower adherence. The analysis on diabetic complications by Cox proportional hazard regression model showed that males have 1.12 times higher risk than females. Therefore, it is expected that diabetic complications can be prevented through careful adherence management and that this study result can be used as basic data for differentiated disease management according to demographic and socioeconomic characteristics.Â